Mortality within the endovascular treatment in Stanford type B aortic dissections - Fioranelli,Alexandre (2011)
BACKGROUND: Endovascular stent-graft repair of aortic dissections is a relatively new procedure, and although apparently less invasive, the efficacy and safety of this technique have not been fully established. OBJECTIVE: To evaluate mortality in patients with complicated Stanford type B aortic dissections submitted to endovascular treatment. METHODS: Clinical, anatomical, imaging and autopsy data of 23 patients with complicated type B aortic dissections were reviewed from November 2004 to October 2007. The main indications for transluminal thoracic stent-grafting included: persistent pain in spite of medical therapy, signs of distal limb ischemia, signs of aortic rupture, progression of aneurismal dilation of the descending aorta during follow-up (defined as a diameter > 50 mm) and the diameter of descending thoracic aorta of 40mm or larger at the onset of aortic dissection. Data were analyzed statistically; all p-values were two-tailed and differences < 0.05 were considered to indicate statistical significance. Continuous variables were expressed as mean (± SD), and medians were compared by the Student's t test. Differences in categorical variables between the groups were analyzed by the Chi-square or Fisher's exact test. RESULTS: The procedure presented primary technical success in 82.6% of patients. Four patients (17.4%) had an incomplete proximal entry seal. Three patients (13%) died within 30 days of the procedure and eight patients (34.8%) died after 30 days. CONCLUSION: Endovascular correction of complicated Stanford type B aortic dissections is a feasible and effective treatment option.